Effects of Enhanced Resistance and Transcriptome Analysis of Twig Blight Disease by Exogenous Brassinolide in Myrica rubra - Zheping Yu; Shuwen Zhang; Li Sun; Senmiao Liang; Xiliang Zheng; Haiying Ren; Xingjiang Qi (MDPI AG, 2023)
Twig blight disease is the primary disease that affects the production of Myrica rubra in China. It was reported that exogenous brassinolide (BL) can improve disease resistance in plants. Here, we examined the effects of exogenous BL on disease resistance, chlorophyll contents, antioxidant enzyme activity, ROS accumulation, and key gene expression of M. rubra to analyze the mechanism of BR-induced resistance of twig blight disease in M. rubra. The results demonstrated that 2.0 mg·L−1 of BL could significantly lessen the severity of twig blight disease in M. rubra. Exogenous BL increased the contents of chlorophyll a, chlorophyll b, carotenoids, and total chlorophyll. Moreover, exogenous BL also significantly enhanced the activity of antioxidant enzymes such as superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), and decreased malondialdehyde (MDA) content and reactive oxygen species (ROS) accumulation in leaves, such as H2O2 and O2·−. Additionally, exogenous BL dramatically up-regulated the expression of pathogenesis-related (PR) genes such as MrPR1, MrPR2, and MrPR10, as well as important genes such as MrBAK1, MrBRI1, and MrBZR1 involved in brassinosteroid (BR) signaling pathway. The transcriptome analysis revealed that a total of 730 common differentially expressed genes (DEGs) under BL treatment were found, and these DEGs were primarily enriched in four Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Based on these findings, nine important candidate genes related to the resistance of twig blight disease under BL treatment were further identified. In this study, we elucidated the effects of exogenous BL on enhancing the resistance of M. rubra to twig blight disease and preliminary analyzed the potential mechanism of resistance induction, which will provide a crucial foundation for the management and prevention of twig blight disease in M. rubra.